Serotyping Scheme for Campylobacter jejuni and Campylobacter coli Based on Direct Agglutination of Heat-Stable Antigens - Frost, J. A. (American Society for Microbiology, 1998)
Campylobacter is now the most frequently reported cause of gastrointestinal disease in England and Wales, yet few isolates are characterized beyond the genus level. The majority of isolates are Campylobacter jejuni (90%), with most of the remainder being Campylobacter coli. We describe an adaptation of the Penner serotyping scheme in which passive hemagglutination has been replaced by detection of heat-stable antigens by direct bacterial agglutination; absorbed antisera are used where appropriate. This scheme has been used to type 2,407 C. jejuni samples and 182 C. coli samples isolated in Wales between April 1996 and March 1997. Forty-seven C. jejuni serotypes were identified, with the 10 most prevalent serotypes accounting for 53% of the isolates tested; 19% of the isolates were untypeable. Only fifteen C. coli serotypes were identified, with three serotypes accounting for 69% of the isolates. This scheme provides a baseline for epidemiological studies of C. jejuni and C. coli.